Construction and expression of Wee1 recombinant protein in Escherichia coli strain BL21 (DE3) - Oktapan, Ladefa Primana; Maulani, Ardela Alief; Ermawati, Netty; Sugiharto, Bambang (Jurnal ILMU DASAR, 2023)
Wee1 is a gene encoding for protein kinase that is located in the nucleus and it plays an essential role in determining the timing of mitosis. Overexpression of Wee1 in rice is resulting in increased plant size. However, the increasing plant size due to the increase of Wee1 protein expression is not elucidated. Immunodiagnostic using specific antibodies against Wee1 protein should be conducted to determine the role of the protein on cell division. This experiment was directed to construct Wee1 in an expression vector for synthesis of recombinant Wee1 protein using three strategies of construction. The three strategies were construction of full length (FL), deletion of putative binding site (BS), and deletion of N-terminal domain (ΔN) of Wee1. Restriction analysis with BamH1/Sal1 of FL-Wee1, BS-Wee1, and ΔN-Wee1 construct resulted in the different DNA fragments with molecular size at 1239, 1176, and 960bp, respectively. This result indicated that the Wee1 fragments have been successfully inserted in the expression plasmid which was further confirmed using DNA sequencing. Colony PCR analysis showed that Escherichia coli strain BL21 (DE3) has been transformed with the constructs. The protein analysis using SDS-PAGE revealed that the recombinant protein of Wee1 synthesized in the E.coli containing ΔN-Wee1 construct, but not in FL-Wee1 and BS-Wee1 constructs. The ΔN-Wee1 protein was synthesized in an insoluble fraction with a molecular size of 38.8 kDa which is the same as the size estimated using the software ExPASy. Interestingly, the level of synthesized ΔN-Wee1 protein was not induced by IPTG concentration. Collectively, the results indicated that the DNA construct of ΔN-Wee1 is suitable for recombinant protein production.